Ответы и объяснения

2012-12-21T06:59:23+00:00

|х+10| + |2x-1| = 16

 

(x+10) + (2x-1) = 16     (x+10) - (2x - 1) = 16     -(x+10) + (2x-1)=16    -(x+10) - (2x-1) = 16

3x-9=16                          -x+11=16                        x-9=16                         -3x+11=16

3x=25                              -x=5                                 x=25                             -3x=5

x=8 1/3                            x=-5                                                                        x= - 1 2/3              

 

2012-12-21T07:07:07+00:00